Tuning the enzyme-like activities of cerium oxide nanoparticles using a triethyl phosphite ligand. (17th May 2022) - Yadav, Nisha; Patel, Vaishwik; McCourt, Luke; Ruppert, Michael; Miller, Michael; Inerbaev, Talgat; Mahasivam, Sanje; Bansal, Vipul; Vinu, Ajayan; Singh, Sanjay; Karakoti, Ajay
Abstract : Tuning the enzyme mimetic activity of cerium oxide nanoparticles using triethylphosphine modifies its enzyme mimetic activities and improves the antimicrobial activity. Abstract : Cerium oxide nanoparticles (CeNPs) exhibit excellent in vitro and in vivo antioxidant properties, determined by the redox switching of surface cerium ions between their two oxidation states (Ce 3+ and Ce 4+ ). It is known that ligands such as triethyl phosphite (TEP) can tune the redox behavior of CeNPs and change their biological enzyme-mimetic activities; however, the corresponding mechanism for such a behavior is completely unknown. Herein, we have studied the effect of TEP in promoting the SOD-enzyme-like activity in CeNPs with high and low Ce 3+ /Ce 4+ ratio, which were synthesized by wet chemical and thermal hydrolysis methods, respectively, and incubated with varying concentrations of TEP. X-ray diffraction, UV-visible, photoluminescence, X-ray photoelectron spectroscopy, and Raman spectroscopy combined with DFT calculations were used to investigate the interaction of TEP on the surface of CeNPs. We observed a clear correlation between TEP concentration and the formation of surface oxygen vacancies. XPS analysis confirmed the increase in Ce 3+ concentration after interaction with TEP. Moreover, we show that TEP's influence depends on the surface Ce 3+ /Ce 4+ ratio. The superoxide dismutase-, catalase-, and oxidase-like activities of CeNPs with high Ce 3+ /Ce 4+ ratio are not affected by TEP interaction, whereas catalase- and oxidase-like activities of CeNPs with low Ce 3+ /Ce 4+ ratio decrease and the SOD-like activity is found to increase upon incubation with different concentrations of TEP. We also demonstrate that TEP interaction does not affect the regeneration of the CeNP surface, while the DFT calculations show that TEP facilitates the formation of defects on the surface of stoichiometric cerium oxide by reducing the oxygen vacancy formation energy. CeNPs with low Ce 3+ /Ce 4+ ratio incubated with TEP also exhibited good antibacterial activity as compared to the CeNPs or TEP alone.